Tuina therapy alleviates knee osteoarthritis by modulating PI3K/AKT/mTOR-mediated autophagy: an integrated machine learning and in vivo rat study - Wang, Zhen; Zhao, Chi; Li, Mengmeng; Zhang, Lili; Diao, Jieyao; Wu, Yiming; Yang, Tao; Shi, Mingwei; Lei, Yang; Wang, Yu; Li, Miaoxiu; Bian, Yanqin; et al. (Frontiers in Immunology, 2025)
BackgroundPrevious studies suggest that Tuina therapy may alleviate knee osteoarthritis (KOA) by modulating the PI3K/AKT/mTOR signaling pathway and autophagy. However, these findings require validation. This study investigated the effect of Tuina monotherapy and Tuina therapy in combination with either a PI3K/AKT/mTOR pathway inhibitor or agonist to investigate whether Tuina therapy alleviates KOA progression by targeting a PI3K/AKT/mTOR pathway to regulate chondrocyte autophagy.MethodsA KOA rat model was established by intra-articular injection of L-cysteine-activated papain solution into the right knee. Rats were randomized to seven groups: Control, Model, LY294002 (PI3K/AKT/mTOR inhibitor), 740 Y-P (PI3K/AKT/mTOR agonist), Tuina, Tuina+LY294002, and Tuina+740 Y-P. The paw withdrawal threshold, knee swelling, and passive range of motion were used as behavioral outcomes. Cartilage degeneration was evaluated using hematoxylin and eosin and Safranin O-Fast Green staining. Chondrocyte ultrastructure and autophagy were observed using transmission electron microscopy. mRNA and protein expression of the PI3K/AKT/mTOR pathway and its downstream biomarkers were quantified using quantitative real-time polymerase chain reaction (RT-qPCR), immunohistochemistry, and western blotting. A secondary analysis was conducted using a support vector machine (SVM) algorithm to predict therapeutic effects and synergistic correlations between indicators.ResultsTuina reduced pain and improved function in KOA model rats, reduced cartilage and chondrocyte damage, increased the cartilage area, and reduced the level of autophagy. Tuina downregulated ATG5, ATG7, ULK1, Beclin-1, LC3II/I and upregulated PI3K, AKT, mTOR, and P62 in cartilage. Compared with the Tuina monotherapy group, the Tuina+LY294002 group had greater pain, joint dysfunction, cartilage degeneration, reduced cartilage area, elevated autophagy, and reduced PI3K/AKT/mTOR pathway activity, whereas Tuina+740 Y-P had the opposite effect. Machine learning validation through SVM achieved 97.62% predictive accuracy. Autophagy was strongly correlated with the PI3K/AKT/mTOR signaling pathway, cartilage degeneration, and behavioral assessment. 740 Y-P enhanced the effect of Tuina therapy, whereas LY294002 attenuated its effect.ConclusionTuina therapy mitigates cartilage degradation and delays KOA progression by activating the PI3K/AKT/mTOR pathway to inhibit chondrocyte autophagy. This study provides insights into the mechanisms through which Tuina exerts its therapeutic effect and highlights its potential as a non-pharmacological intervention for KOA.